Environmental, Social and Governance Ratings - Stamenova, Radostina (Research Papers, 2024)
With the expansion of sustainable investment practices, environmental, social and governance ratings (ESG ratings) are gaining more and more popularity among financial market participants. ESG ratings reduce information asymmetry, helping investors to identify companies that, in addition to being financially creditworthy, are also socially and environmentally responsible. On the other hand, understanding the information carried by the ratings is hampered by a lack of consistency, transparency, and a common regulatory framework, which undermines trust in them. The purpose of this article is to clarify the informational value of ESG ratings by comparing the methodologies, rating scales and market practices of their leading providers.
Keywords: Sustainable investing; ESG ratings; Credit ratings